Hambatan Guru dan Pelayanan Sekolah Minggu di Gereja Kristen Jawa Jebres Surakarta - Tanto Kristiono; Deo Putra Perdana (Sekolah Tinggi Teologi Baptis, Jakarta, 2019)
Children will later continue the baton of church service. They will be responsible for the condition of the church in the future. Sunday schools are present as church institutions to prepare them to become candidates for church leaders. The Church needs people who are willing to become Sunday school teachers. The fact is that it is not easy to become a Sunday school teacher, they must understand and learn about the various competencies that must be possessed to become a good teacher and servant of God. This study was conducted to obtain empirical evidence about the effect of teacher barriers on the motivation for Sunday school services in Jebres Javanese Christian Church Surakarta. The population in this study were GKJ Jebres Surakarta Sunday school teachers, totaling 20 people. In the study used data collection techniques that are considered suitable, namely questionnaire (questionnaire). In this study, the independent variables are barriers to Sunday school teachers, while the dependent variable is the motivation of Sunday school services at GKJ Jebres Surakarta. The collected data will be analyzed using correlation test and simple regression analysis at a significance level of 5%. The results showed that there was a very strong correlation between the obstacles of Sunday school teachers and the motivation of Sunday school services in Jebres Javanese Christian Church. The results also show that the constraints of Sunday school teachers have a significant effect on the motivation of Sunday school services in Jebres Javanese Christian Church. Abstrak Anak-anak nantinya akan meneruskan tongkat estafet pelayanan gereja. Merekalah yang akan bertanggung jawab dengan kondisi gereja di masa mendatang. Sekolah minggu hadir sebagai lembaga gereja guna mempersiapkan mereka untuk menjadi calon pemimpin gereja. Gereja membutuhkan orang-orang yang bersedia menjadi guru sekolah minggu. Faktanya tidak mudah untuk menjadi seorang guru sekolah minggu, mereka harus memahami dan belajar tentang berbagai kompetensi yang harus dimiliki untuk menjadi seorang guru sekaligus pelayan Tuhan yang baik. Penelitian ini dilakukan untuk memperoleh bukti empiris tentang pengaruh hambatan-hambatan guru terhadap motivasi pelayanan sekolah minggu di Gereja Kristen Jawa Jebres Surakarta. Populasi dalam penelitian ini adalah guru-guru sekolah minggu GKJ Jebres Surakarta yang berjumlah 20 orang. Dalam penelitian digunakan tehnik pengumpulan data yang dianggap cocok, yakni angket (kuesioner). Dalam penelitian ini variabel bebasnya adalah hambatan-hambatan guru sekolah Minggu, sedangkan yang menjadi variabel terikat adalah motivasi pelayanan sekolah Minggu di GKJ Jebres Surakarta. Data yang terkumpul akan dianalisis dengan menggunakan uji korelasi dan analisis regresi sederhana pada tingkat signifikansi sebesar 5%. Hasil penelitian menunjukkan bahwa terdapat korelasi yang sangat kuat sekali antara hambatan-hambatan guru sekolah Minggu dengan motivasi pelayanan sekolah Minggu di Gereja Kristen Jawa Jebres. Hasil penelitian juga menunjukkan bahwa hambatan-hambatan guru sekolah Minggu berpengaruh signifikan terhadap motivasi pelayanan sekolah Minggu di Gereja Kristen Jawa Jebres.